The influence of interest rate risk ratio and capital adequacy ratio on profit growth in banking companies listed on the stock exchange - Ngatinem, Ngatinem; Fauzi, Indra (Jurnal Mantik, 2024)
Banks are faced with the challenge of ensuring that they have the right strategy in managing IRR and maintaining CAR within the required limits. A decline in profit growth can be an indicator that banks may be facing difficulties in managing this risk effectively. In this study, the population used was banking companies listed on the IDX (Indonesia Stock Exchange) for the period 2021–2023, namely 33 companies. The type of research used by the author in this study is descriptive and quantitative. The sampling technique used in this study was the purposive sampling method. Based on the characteristics of the sampling above, the companies that were sampled in this study were 16 companies out of 33 banking companies listed on the Indonesia Stock Exchange during 2021-2023. The location of this research is in banking companies listed on the official website of the Indonesia Stock Exchange www.idx.co.id and the official website of banking companies. Based on the influence of each variable simultaneously, it can be seen that the F count value (5.652) > F table (3.20) with a significant level of 0.006 <0.05 . So this shows that H3 is accepted Interest Rate Risk Ratio and Capital Adequacy Ratio have a significant effect on profit growth. The effect of Interest Rate Risk (IRR) and Capital Adequacy Ratio (CAR) on profit growth has been studied in the context of banking. Based on the results of the research that has been done, it can be concluded that In the Interest Rate Risk Ratio the t count value is 1.729 > t table (1.678) (nk = 48-2-1 = 45), then there is a significant effect on profit growth In the Capital Adequacy Ratio the t count value is 3.785 > t table (1.679) (nk = 48-2-1 = 45), then there is a significant effect on profit growth. Based on the influence of each variable simultaneously, it can be seen that the Fcount value (5.652) > Ftable (3.20) with a significant level of 0.006 < 0.05 . So this shows that H3 is accepted. Interest Rate Risk Ratio and Capital Adequacy Ratio have a significant effect on profit growth